Social Capital of Fisher’s Group at the Bagan Deli Village (Case Study at Berkah Bahari Group Medan Belawan Sub-district, Medan City, North Sumatera Province) - Sebayang, Elseria Br; Amrifo, Viktor; ', Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Social capital is the ability of a fisherman or fishermen group who work together to build a network to achieve the common goals in improving the quality of life that includes trust, institutions and social networks. This research is about social capital that is formed on fishermen group in Bagan Deli Village, Medan Belawan Sub-district, Medan city, North Sumatera Province. The method used in this research is case study by in-depth interview, observation and documentation study which is analyzed qualitative descriptive.The results showed that the existence of social capital in the group of fishermen Berkah Bahari can be seen through the dimensions of bonding, bridging and linking. Berkah Bahari fishermen groups have forms of social capital such as trust/trusting relationships, institutions, and good social networks in the level of individuals / members within the group or outside the group. The most dominant form of social capital in the Berkah Bahari fishermen group and fellow fishermen other than the Berkah Bahari fishermen group is the relation of mutual trust and social network compared by the relatively low institutions.Keywords: social capital, fisher group,Berkah Bahari, Bagan Deli